The political implications of North Sea oil and gas : under the auspices of the Norwegian Inst.of Internat.Affairs, Oslo, and the Royal Inst.of Internat.Affairs, London - Saeter, Martin (Universitetsforlaget, 1975)
Seven papers which were presented to an international conference held in Torsberg, Norway. All have been revised for publication and are followed by a summary of the discussion in the relevant session.